Mechanism of metabolic memory: progression in diabetic nephropathy—a descriptive review - Farhana Begum; Karpagavel Lakshmanan (Egyptian Journal of Medical Human Genetics)
Abstract Diabetes mellitus and its complications exploit significantly impact global human well-being and economic burden. Previous studies and clinical trials have provided insights into the concept of metabolic memory, which sustains even after hyperglycemia has been resolved, causing diabetic complications completely. The term “metabolic memory” refers to the body’s abnormal metabolism, which can have long-term effects and influence both health and disease conditions. It involves various molecular processes causing cellular shifts, tissue and organ dysfunctions, disease progression, and effects on offspring. The conceptual framework of metabolic memory is defined and strengthened, offering a comprehensive understanding of the underlying causes of diabetic nephropathy (DN) and providing a potential new approach for diagnosing and treating the disease. In this review, we elucidated the importance, characteristics, cellular and molecular importance, and therapeutic intervention to eradicate metabolic memory in DN once hyperglycemia has been eliminated. The regulation of metabolic memory is assisted based on an epigenetic mechanism. Therefore, this report traces the significant factors involved in regulating epigenetic modifications such as DNA methylation, histone modification, and chromatin remodeling. This mechanism significantly triggers epigenetic regulation, leading to glucose stress, oxidative stress induction, and apoptosis, causing DN. It occurs beyond various signaling cascades, resulting in alterations in transcription factors and receptor molecules, which enhance the metabolic memory in the post-sustenance of hyperglycemia. This condition can be modulated based on therapeutic interventions involving lifestyle modification and the inclusion of natural substances like bioactive compounds, polyphenols, and terpenoids in the diet, followed by medications acting as epigenetic modifiers.